Neoadjuvant multimodal treatment of pancreatic ductal adenocarcinoma. (February 2016) - Silvestris, Nicola; Longo, Vito; Cellini, Francesco; Reni, Michele; Bittoni, Alessandro; Cataldo, Ivana; Partelli, Stefano; Falconi, Massimo; Scarpa, Aldo; Brunetti, Oronzo; Lorusso, Vito; Santini, Daniele; et al.
Highlights: Preoperative staging and definition of initially resectable PDAC, BRPC and LAPC. Neoadjuvant treatment for resectable PDAC. Primary treatment for BRPC and LAPC. Significance of histopathological response after primary treatments and prognostic/predictive biomarkers. Ongoing clinical trials. Abstract: Treatment of pancreatic ductal adenocarcinoma (PDAC) is increasingly multidisciplinary, with neoadjuvant strategies (chemotherapy, radiation, and surgery) administered in patients with resectable, borderline resectable, or locally advanced disease. The rational supporting this management is the achievement of both higher margin-negative resections and conversion rates into potentially resectable disease and in vivo assessment of novel therapeutics. International guidelines suggest an initial staging of the disease followed by a multidisciplinary approach, even considering the lack of a treatment approach to be considered as standard in this setting. This review will focus on both literature data supporting these guidelines and on new opportunities related to current more active chemotherapy regimens. An analysis of the pathological assessment of response to therapy and the potential role of target therapies and translational biomarkers and ongoing clinical trials of significance will be discussed.